Instantly Decodable Network Coding Schemes for In-Order Progressive Retransmission - Wang, Shujuan; Gong, Chen; Wang, Xiaodong; Liang, Mangui (IEEE communications letters, 2013)
We propose network coding schemes for a broadcast system where the source packets exhibit a hierarchical structure, such that the successful information retrieval of a packet at a certain layer relies on the correct receptions of the packets in the previous layers. Assuming the entire transmission consists of two stages, the broadcast stage and the retransmission stage, for progressive packet information decoding, we propose novel source packet combining schemes for retransmission based on network coding. The objective is to reduce the number of retransmissions for decoding certain fraction of the source packets. The proposed schemes can be applied to scalable video broadcast systems.